Stress, metabolic and serum muscle-derived enzymes response of horses employed in wooded area and field trekking courses - Arfuso, F.; Piccione, G.; Trimarchi, F.; Panzera, M. F.; Giannetto, C. (Journal of Equine Veterinary Science, 2022)
Horse trekking is a non-competitive sport that, as other kinds of exercise, involves skeletal muscle effort and may implicate significant energy expenditure leading to stress. The aim of the current study was to assess the effect of trekking on metabolic and stress response as well as muscle damage markers in clinically healthy horses. Thirty horses were equally divided in 3 groups according to trekking course: Group A (trekking course 15 km long), Group B (trekking course 35 km long starting;), Group C (three trekking courses for three consecutive days; during the first day the trekking course was 25 km long, Group C1; during the second day the trekking course was 40 km long, Group C2; during the third day the trekking course was 25 km long, Group C3). Blood samples were collected from each horse before trekking (TPRE), after 5 min (TPOST) and 1 h from the trekking end to assess lactate, glucose, total proteins, non-esterified fatty acids (NEFAs), creatinine, aspartate aminotransferase (AST), creatine phosphokinase (CPK), lactate dehydrogenase (LDH) and cortisol concentration. Higher cortisol, lactate, glucose, NEFAs, creatinine, CPK, LDH and AST values were found after trekking than rest (P < .001). Horses of Groups C2 and C3 showed higher values of the investigated haematochemical parameters and muscle enzymes than Groups A and B. The findings suggest that trekking induces a metabolic reaction accompanied by an acute stress response in horses and underline that this recreational exercise, if not associated with the adequate recovery period, can increase the probability of muscle damage.